To solve the equation \(-\frac{3}{5}x = \frac{2}{5}\), you can isolate \(x\) by multiplying both sides of the equation by the reciprocal of \(-\frac{3}{5}\).
Here are the steps:
- Multiply both sides by \(-\frac{5}{3}\):
\[ x = \frac{2}{5} \cdot -\frac{5}{3} \]
- Simplify the right side:
\[ x = \frac{2 \cdot -5}{5 \cdot 3} \]
- This simplifies to:
\[ x = \frac{-10}{15} \]
- Reduce the fraction by dividing the numerator and the denominator by 5:
\[ x = \frac{-2}{3} \]
So the solution is:
\[ x = -\frac{2}{3} \]